Politeness Strategy Given by Costumer Services at Pawnshop Places - Nurul Lathifah (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2017)
This paper purpose to analyze the politeness strategies by costumer service the pawnshop and cash collateral. Following this research, the researchers want to analyze politeness strategies are dictated by customer services in the places of pawning in Balikpapan. It is focused to observe grammar and courtesy of employees of that places that will serve its customers. Since over here it can be said the costumer service has the thoughtful characteristic to serve the consumer such as their reaction about strategies to pull of consumer to join and believing. In the pawning place which is we are the researchers to looking for they are have the different threatening to convey the strategies and they have the method to expressive their threats like giving the brochure and straight to many ways about question.